UNRAVELING BRAND EQUITY: STRATEGIES TO IMPROVE CONSUMER PURCHASE DECISION - Tekat Sukomardojo; Frasto Biyanto; Reni Sara Indrawati; Khotimatul Barki; Syamsuddin Syamsuddin (Branding: Jurnal Manajemen dan Bisnis, 2023)
Marketing strategy is an important element in the business world. One of the objectives of the marketing strategy is to increase consumer buying decisions. This can be done by utilizing the equity of a brand. This research will aim to look at how to increase consumer purchasing decisions by using brand equity. This type of research is descriptive qualitative research. The data used in this study comes from various research results and previous studies which still have relevance to the content of the research. The results of this study then found that brand equity cannot be ignored as a driver of consumer purchasing decisions. There are several strategies to increase brand equity. This can be done by conducting marketing campaigns to increase brand awareness, by collaborating with artists or influencers. By using these various strategies, consumer purchasing decisions can be significantly improved.